2015
DOI: 10.4103/2278-330x.173175
|View full text |Cite
|
Sign up to set email alerts
|

Fertility preservation in young patients with cancer

Abstract: Infertility can arise as a consequence of treatment of oncological conditions. The parallel and continued improvement in both the management of oncology and fertility cases in recent times has brought to the forefront the potential for fertility preservation in patients being treated for cancer. Many survivors will maintain their reproductive potential after the successful completion of treatment for cancer. However total body irradiation, radiation to the gonads, and certain high dose chemotherapy regimens ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 42 publications
0
16
0
2
Order By: Relevance
“…Another important perspective application of the PSO1 cells lies in the potential contributions to solve fertility problems and the long‐term cryopreservation of germ cells. In human, with its feasibility of fertility preservation, cryobanking of ovarian tissue has become increasingly common in countries that have well‐established fertility centers . There has been a number of successful birth cases after autotransplantation of cryopreserved ovarian tissues in both human and mouse .…”
Section: Discussionmentioning
confidence: 99%
“…Another important perspective application of the PSO1 cells lies in the potential contributions to solve fertility problems and the long‐term cryopreservation of germ cells. In human, with its feasibility of fertility preservation, cryobanking of ovarian tissue has become increasingly common in countries that have well‐established fertility centers . There has been a number of successful birth cases after autotransplantation of cryopreserved ovarian tissues in both human and mouse .…”
Section: Discussionmentioning
confidence: 99%
“…While our understanding of the effect of cachexia on mammalian GSC lineages is limited, cachetic patients are often insulin resistant (Honors and Kinzig 2012), and chronic inflammation, found in many cancers (Crusz and Balkwill 2015), can lead to Interleukin-6 mediated hyperactivation of the hypothalamic-gonadal-pituitary axis (Raber et al 1997). Therefore, although it is clear that many cancer treatments can impair fertility (Suhag et al 2015; Vakalopoulos et al 2015), it is also possible that the physiological changes caused by the tumors themselves may also have effects on the germ line of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several innovative techniques, including ovarian tissue cryopreservation, are being actively investigated. Current techniques are limited by the patient's sexual immaturity, and all available approaches for children are experimental (48,49). Several studies have shown that gonadotropin-releasing hormone agonists when used with chemotherapy protect against ovarian failure, reducing the risk of early menopause and improving prospects for fertility (50).…”
Section: Fertility Preservationmentioning
confidence: 99%